Surgical Interventions for Functional Constipation: An Update - Vilanova-Sanchez, Alejandra; Levitt, Marc A. (European Journal of Pediatric Surgery, 2020)
Chronic idiopathic constipation, also known as functional constipation, is defined as difficult and infrequent defecation without an identifiable organic cause. Medical management with laxatives is effective for the majority of constipated children. However there is a subset of patients who may need evaluation by a surgeon. As constipation progresses, it can lead to fecal retention and rectal and sigmoid distension, which impairs normal colorectal motility. Surgical interventions are influenced by the results of: a rectal biopsy, transit studies, the presence of megacolon/megarectum on contrast enema, the degree of soiling/incontinence, anorectal manometry findings, and colonic motility evaluation. In this review, we describe the different surgical options available (intestinal diversion, antegrade enemas, sacral nerve stimulation, colonic resections, and Botulinum toxin injection) and provide guidance on how to choose the best procedure for a given patient.
Keywords: functional constipation; pediatric colorectal surgery; colonic motility; surgery for pediatric constipation